The impact of online upward social comparisons on cyberbullying in the post-epidemic era: a moderated mediating model - Yuan, Guangjie; Cheng, Zihan; Ju, Wei (Frontiers in Psychology, 2025)
IntroductionAgainst the backdrop of the post-pandemic era, this study systematically examines the antecedents and underlying mechanisms of cyberbullying among college students. Building upon the social comparison theory, we particularly investigate how upward social comparison (USC) contributes to cyberbullying through the dual mediating pathways of cognitive and emotional relative deprivation (RD). Importantly, we further explore the moderating role of belief in a just world (BJW) in this psychological process.MethodsTo test our theoretical framework, we collected survey data from 526 undergraduates and employed structural equation modeling with Bootstrap resampling.ResultsThe analysis yielded two major findings: First, upward social comparison (USC) was significantly positively associated with cyberbullying, mediated by cognitive and emotional relative deprivation. Second, belief in a just world (BJW) negatively moderated the relationship between relative deprivation (RD) and cyberbullying. Specifically, both general and personal BJW weakened the positive link between cognitive relative deprivation (CRD) and cyberbullying. Similarly, emotional relative deprivation (ERD) effects were moderated by general and personal BJW.DiscussionThe findings not only expand the applicability of the social comparison theory and BJW but also provide empirical evidence for college mental health education.